Intellectual Property Rights, Quality of Institutions, and Foreign Direct Investment into Developing Asia - Minsoo Lee; Donghyun Park (Asian Development Bank (ADB), 2013)
Developing Asian countries are strengthening their intellectual property rights (IPR) regime as they themselves become producers of intellectual property. At the same time, developing Asia has attracted large amounts of foreign direct investment (FDI) and this trend is expected to continue in light of the region's strong growth prospects. In this paper, we explore the relationship between IPR and FDI in developing Asia. To do so, we develop a theoretical model which predicts that stronger IPR protection attracts more FDI in countries with small informal economies - i.e., strong institutions - but not in countries with large informal economies - i.e., weak institutions. Our empirical analysis, based on a threshold effect model, yields some evidence which supports our theoretical model.
hdl:11540/2089
Keywords: F23; O17; O34; 330; intellectual property rights; foreign direct investment; informal economy; institutions; Asia